Customer selection criteria towards saving in Islamic banks at Tanah Merah / Munirah Mahshar - Mahshar, Munirah (UNIVERSITI TEKNOLOGI MARA, 2012)
This project paper attempts to identify the customer selection criteria towards savings in Islamic bank at Tanah Merah. Savings can be depicted as amount of current income which is not spent on consumption. Saving will help people to aintain a higher level of investment, which is a key determinant of economic growth. It will lead to an economic growth in order to stabilize a Malaysian economics. The empirical evidence from many literatures witnessed that some of independent variables (corporal efficiency, shariah compliance and convenience) have significant effect to the dependent variable (saving). So, the primarily focus of this paper is, attempt to study on the relationship between independent variables (corporal efficiency, shariah compliance and convenience ) affects on the dependent variable, savings in Islamic bank at Tanah Merah. This is important because this area of study has not been greatly researched in Malaysia. With that, corporal efficiency, shariah compliance, and convenience will be put as independent variables and savings will be put as dependent variable. The aims of this present study are threefold : firstly to identify factors that contribute to savings in Islamic bank at Tanah Merah, to know the relationship between dependent variable and independent variables towards saving, and lastly, to identify the major contribution in saving. A multiple regression model is employed to find the relationship between dependent and independent variables. All the data collected from 100 numbers of respondents. The result indicates that corporal efficiency and convenience show a positive relationship towards savings at Islamic bank at Tanah Merah. Meanwhile, shariah compliance shows an insignificant relationship towards the savings in Islamic banks at Tanah Merah. Hence, shariah compliance cannot give an impact towards saving in Islamic bank at Tanah Merah.